Peripheral leukemia burden at time of apheresis negatively affects the clinical efficacy of CART19 in refractory or relapsed B-ALL - Biping Deng (Elsevier, 2021)
Our previous clinical study achieved complete remission (CR) rates of >90% following chimeric antigen receptor T cells targeting CD19 (CART19) treatment of refractory/relapsed B cell acute lymphoblastic leukemia (r/r B-ALL); however, the influence of the leukemia burden in peripheral blood (PB) blasts remains unclear. Here, we retrospectively analyzed 143 patients treated with CART19 (including 36 patients with PB blasts) to evaluate the effect of peripheral leukemia burden at the time of apheresis. One hundred seventeen patients with high disease burdens achieved 91.5% CR or incomplete count recovery CR and 86.3% minimal residual disease-negative CR, and 26 patients with low disease burdens obtained 96.2% MRD− CR. Collectively, 9 of 36 (25%) patients with PB blasts and 2 of 107 (1.87%) patients without PB blasts did not respond to CART19 therapy. The leukemia burden in PB negatively influenced ex vivo cell characteristics, including the transduction efficiency of CD3+ T cells and their fold expansion, and in vivo cell dynamics, including peak CART19 proportion and absolute count, fold expansion, and persistence duration. Further studies showed that these patients had higher programmed death-1 expression in CART19 products. Our data imply that PB blasts negatively affected CART19 production and the clinical efficacy of CART19 therapy in patients with r/r B-ALL.